Perceptions of special education pre-service teachers regarding the implementation of a neuroscience motifs-based teacher training program - Luzzatto, Efrat; Shalom, Maya; Rusu, Alina S. (Frontiers in Education, 2024)
While the interest in the connection between neuroscience and education continues to increase, there is a gap between the declarative statements regarding its importance and the small number of programs that put it into practice. The perceptions of the participants in these programs might offer valuable insights regarding the applied values of this connection. This study seeks to contribute to the accumulated research knowledge by using a qualitative analysis approach regarding the perceptions of pre-service teachers (PSTs) in a special education track program. The PSTs participated in a unique training program called the “Neuroscience Motifs-based Teacher Training Program” (NMTTP) that was presented as part of a reading course. Findings reveal mostly positive perceptions of the PSTs regarding the importance, relevance and contribution of neuroeducation to education, from a professional & personal perspective. In addition, the findings expand the current literature in two aspects: (1) the potential benefits that neuroscience can grant to education in general, and to special education in particular; (2) the contribution of knowledge on neural basis for PSTs to a sense of perspective, patience and empathy toward challenging students, by understanding some of the ongoing processes in their students’ brains.